DIGITAL ENTREPRENEURSHIP: THE ROLE OF TECHNOLOGY READINESS AND SOCIAL MEDIA UTILIZATION IN MALANG EAST JAVA MSMES - Taufik, Irfan; Sudarmiatin, Sudarmiatin; Wardana, Ludi Wishnu (Nusantara Economics and Entrepreneurships Journals, 2024)
This study explores the role of technology readiness and social media utilization in supporting digital entrepreneurship among Micro, Small and Medium Enterprises (MSMEs). In a dynamic digital era, the ability of MSMEs to adopt new technologies and effectively utilize social media is a key factor in achieving growth and competitiveness. Technological readiness includes infrastructure, human resource skills, and a culture of innovation, all of which contribute to operational efficiency and the ability to adapt to market changes. Meanwhile, social media offers a platform for MSMEs to reach a wider audience, build relationships with customers, and increase brand awareness at an affordable cost. This article analyzes how these two elements interact and influence business innovation and growth. It also discusses the challenges MSMEs face in the digital transformation process and strategies to overcome these obstacles. With a deeper understanding of the role of technology and social media, MSMEs can capitalize on the opportunities of the digital era to achieve long-term success. This research takes a case study in Malang City with 100 respondents from the results of calculations using the slovin formula from a population of 21,270 MSMEs in Malang City based on data obtained from the Government of Malang. The results showed that the variables studied had an effect based on the results of data analysis that had been carried out with several stages until finally at the test stage the coefficient of determination analysis showed that technological readiness and social media utilization had an effect of 67.2% on the performance of MSMEs in Malang city, while the remaining 32.8% percentage results were influenced by other variables outside of the variables of this study